Enzymatic Bioprospecting of Fungi Isolated from a Tropical Rainforest in Mexico - Karla Peraza-Jiménez; Susana De la Rosa-García; José Javier Huijara-Vasconselos; Manuela Reyes-Estebanez; Sergio Gómez-Cornelio (Journal of Fungi, 2021)
The humid tropical environment provides an ideal place for developing a high diversity of plants; this is why it is an interesting site for the enzymatic bioprospecting of fungi that are responsible for the recycling of organic matter in an efficient and accelerated way and whose enzymes could have multiple biotechnological applications. For this study, 1250 isolates of macroscopic and microscopic fungal morphotypes were collected from soil, leaf litter, and wood. One hundred and fifty strains (50 from each source) were selected for the enzymatic screening. From the first phase, 51 strains with positive activity for laccase, protease, amylase, xylanase, and lipase enzymes were evaluated, of which 20 were isolated from leaf litter, 18 from the soil, and 13 from wood. The 10 best strains were selected for the enzymatic quantification, considering the potency index and the production of at least two enzymes. High laccase activity was detected for Trametes villosa FE35 and Marasmius sp. CE25 (1179 and 710.66 U/mg, respectively), while Daedalea flavida PE47 showed laccase (521.85 U/mg) and protease activities (80.66 U/mg). Fusarium spp. PH79 and FS400 strains had amylase (14.0 U/mg, 49.23 U/mg) and xylanase activities (40.05 U/mg, 36.03 U/mg) respectively. These results confirm the enzymatic potential of fungi that inhabit little-explored tropical rainforests with applications in industry.